MODIFICATIONS OF VOWELS IN CONNECTED SPEECH (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2023)
This article delves into the intricate changes vowels undergo in the  context of connected speech. It explores two key modifications: vowel reduction and  elision. The discussion encompasses how these alterations occur in natural conversation,  impacting pronunciation for efficiency and clarity. The annotation highlights the  influence of surrounding sounds and regional variations on vowel modifications. It also  emphasizes the significance of understanding these shifts for improved language  comprehension, particularly for non-native speakers. Overall, the article illuminates the  dynamic nature of spoken language and its nuanced variations, offering valuable insights  into the subtleties of communication